098 Differential effects of hypertrophy secondary to hypertension and aortic stenosis on coronary haemodynamics. (22nd September 2015) - Hadjiloizou, N; Davies, J; Baksi, J; Malik, I; Hughes, A; Foale, R; Parker, K; Francis, D; Mayet, J
Abstract : It is known that subjects with left ventricular hypertrophy (LVH) have adverse cardiovascular outcomes and abnormal coronary haemodynamics. LVH is common to aortic stenosis (AS) and arterial hypertension (HT) but the pattern of abnormal coronary flow may be different in these two conditions. The aim of this study was to quantify the coronary haemodynamics present in each of these conditions and determine the relative contribution of LVH, haemodynamic loading and diastolic time. Thirty-one patients (mean age 63±12 years, 18 female) with unobstructed coronary arteries, (10 with LVH and severe AS, 11 with LVH secondary to HT and no AS (LVH-HT), 10 with no LVH and no AS) underwent simultaneous pressure and Doppler velocity measurements with sensor-tipped intra-arterial wires in each of the left coronary arteries to measure coronary pressure and flow and derive wave intensity. Despite the lower aortic pressure (93±18 mm Hg vs 115±15, p<0.01), subjects with AS had higher resting coronary flow (per gram of LVH) than patients with LVH-HT (3.24±1.20 ml/g vs 0.97±054 ml/g, p<0.001). AS subjects generated a significantly larger microcirculatory-originating suction wave than LVH-HT (31.1 (20.4–47.4)×10 3 Wm −2 s −1 vs 12.2 (8.4–17.5)×10 3 Wm −2  s −1, p<0.05). There was a negative correlation of LVH with the suction wave in subjects without AS (r=−0.49, p<0.03) but not in AS (r=−0.08, p=0.83). Instead, in AS the extent of the suction wave correlated with left ventricular cavity pressure (r=0.84, p<0.001) and diastolic time (r=−0.62, p<0.001). LVH accounts for the impaired coronary flow in HT but not in AS. The enhanced extravascular force in AS overwhelms any local impairment that might be caused by ventricular hypertrophy and accounts for the greatly increased resting coronary flow.